2001
DOI: 10.1088/0022-3727/34/24/310
|View full text |Cite
|
Sign up to set email alerts
|

The barrier effect in three-layer solid dielectrics in quasi-uniform electric field

Abstract: In this paper, the experimental results of the study of the behaviour of three-layer solid dielectrics in high electric field are presented. The breakdown voltage and the breakdown channel forms depend on factors such as the position of the boundaries between layers in the gap, the ratio of permittivities of layer materials, and the homogeneity of barrier materials. It was found that polarization plays the main role in the barrier effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
25
0
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 10 publications
(14 reference statements)
2
25
0
5
Order By: Relevance
“…A graphic representation of the ANOVA results is shown in Figure 6, along with the average breakdown strengths of the films when AlON or HfON is the bottom layer. This same trend was seen in the polymer films reported by Agoris et al [10] although the results are slightly more pronounced with the three and five layer films. This indicates that the layering of dielectric materials is a simple method to increasing the breakdown strength of a capacitor device.…”
Section: Multilayer Filmssupporting
confidence: 87%
See 2 more Smart Citations
“…A graphic representation of the ANOVA results is shown in Figure 6, along with the average breakdown strengths of the films when AlON or HfON is the bottom layer. This same trend was seen in the polymer films reported by Agoris et al [10] although the results are slightly more pronounced with the three and five layer films. This indicates that the layering of dielectric materials is a simple method to increasing the breakdown strength of a capacitor device.…”
Section: Multilayer Filmssupporting
confidence: 87%
“…ACCEPTED MANUSCRIPTRecent polymer nanocomposite and layered inorganic gate dielectric research has suggested that conduction current, breakdown strength, and dielectric constant of a dielectric can be influenced by tailoring the thickness, composition, and orientation of interstitial layers[6,10].Agoris et al achieved this through the insertion of a thin, high dielectric constant (high-k) barrier layer into the middle of a polymer dielectric. They achieved increases in breakdown strength of up to 50%[10].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…4, 5 The motivation for a multilayered structure is to take advantage of the barrier effect. [6][7][8][9] It is well known that introducing a component that presents a barrier to the propagation of the electrical breakdown channel can increase the dielectric strength of the material. 10 A multilayered polymer material provides many barriers to the propagation of a breakdown through the film.…”
mentioning
confidence: 99%
“…The dependence of electrical properties of filled composites on the applied electric fields is well established [2,13]. As filler particles become points of local field increase, due to the large differences or contrast between permittivity and conductivity at the filler-matrix interface, it is crucial to understand the high field losses present in the system arising due to the various contributions, i.e., dc conduction and space charge.…”
Section: Displacement-electric Field Loopsmentioning
confidence: 99%